2012
DOI: 10.1167/iovs.12-10007
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Lutein in Retinal Ischemic/Hypoxic Injury: In Vivo and In Vitro Studies

Abstract: PURPOSE. Lutein protects retinal neurons by its anti-oxidative and anti-apoptotic properties in ischemia/reperfusion (I/R) injury while its anti-inflammatory effects remain unknown. As Müller cells play a critical role in retinal inflammation, the effect of lutein on Müller cells was investigated in a murine model of I/R injury and a culture model of hypoxic damage.METHODS. Unilateral retinal I/R was induced by a blockade of internal carotid artery using the intraluminal method in mice. Ischemia was maintained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
97
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 69 publications
(74 reference statements)
7
97
1
1
Order By: Relevance
“…Tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and other inflammatory mediators, through a series of cascade reactions, may induce leukocyte infiltration to the lesions, block the capillaries, and damage the microvascular endothelium, leading to low perfusion. The infiltrating leukocytes further produce large amounts of cytokines, chemokines, and matrix met- alloproteinases (MMPs), causing blood-retinal barrier destruction and aggravating the injury, ultimately resulting in retinal neuronal cell death (23,24). However, there are also some protective cytokines in RIR injury.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and other inflammatory mediators, through a series of cascade reactions, may induce leukocyte infiltration to the lesions, block the capillaries, and damage the microvascular endothelium, leading to low perfusion. The infiltrating leukocytes further produce large amounts of cytokines, chemokines, and matrix met- alloproteinases (MMPs), causing blood-retinal barrier destruction and aggravating the injury, ultimately resulting in retinal neuronal cell death (23,24). However, there are also some protective cytokines in RIR injury.…”
Section: Discussionmentioning
confidence: 99%
“…Together these results strongly support the hypothesis that lutein given orally may have protective effects on organs and tissues. Lutein seems to have not only antioxidant activity but also anti-inflammatory action as it has been recently reported [36]. Lutein inhibits arachidonic acid release from a macrophage cell line, blocking cytosolic phospholipase A2 activity [37].…”
Section: Discussionmentioning
confidence: 99%
“…Various carotenoids are present in human plasma, but only the xanthophylls lutein and zeaxanthin are found in retina in considerable amounts (Junghans et al, 2001). Lutein, a potent antioxidant, has been applied in human clinical trials and shown to improve vision and retard the progression of AMD and cataract development (Chasan-Taber et al, 1999;Itagaki et al, 2006;Li et al, 2009;Li and Lo, 2010;Richer et al, 2007;Richer et al, 2004), however the mechanism of protection is unclear and the role of lutein in ischemic injury is limited (Li et al, 2012). In vitro studies show lutein can penetrate into cells and scavenge intracellular H 2 O 2 preventing cell damage (Li and Lo, 2010) suggesting a possible therapeutic benefit to antioxidant intervention for diseases linked to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%